CORRELATIVE STUDY OF LEAD ION REMOVAL EFFICIENCY FROM AQUEOUS SOLUTION USING ACTIVATED CARBONIZED AFRICAN STAR APPLE SEED COAT (Chrysophyllum albidum) AND ACTIVATED Lophira alata CARBONIZED SAWDUST - MOSES O.,; PEREGRINO A. A., (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
Water is very useful to human existence. Lead accumulation along the food chain can result in serious health hazards. This research was designed to examine the removal efficiency of Pb2+ ion from aqueous solution using activated carbonized African star apple seed coat (ACASASC) and activated lophira alata carbonized sawdust (ALACS) obtained from Benin City, Edo State, Nigeria. The ACASASC and ALACS were prepared by carbonization and activated using KOH. ACASASC and ALACS were physicochemically characterized. The adsorption process of Pb2+ ions on ACASASC and ALACS was studied using the batch adsorption experiments and the data obtained were analyzed using adsorption isotherm model. The SEM picture, the iodine number and porosity determination revealed that ACASASC had a larger surface area than ALACS. FTIR spectrum revealed the ACASASC possessed higher amount of oxygen carrying functional groups compared to that of ALACS, indicating that the ACASASC possess higher adsorption capacity than ALACS. The quantity (qm) of Pb2+ ions adsorbed by ALACS was lower compared to that of ACASASC. The adsorption process of Pb2+ ions onto ACASASC and ALACS was physical and spontaneous. The adsorption isotherm model revealed that ACASASC is a more efficient removal of Pb2+ ions from aqueous solution compared to ALACS.